A P-doped covalent carbon-nitrogen framework with confined single-atom Mn dispersion and its preparation method and application

By dispersing single atom Mn in the covalent carbon-nitrogen framework in the covalent carbon-nitrogen framework and introducing P doping, a P-doped covalent carbon-nitrogen framework with confined single atom Mn dispersed P-doped covalent carbon-nitrogen framework was constructed, which solved the problems of insufficient catalytic sites and limited charge separation capabilities of existing photocatalytic materials, and achieved efficient photocatalytic CO2 reduction performance.

CN116196979BActive Publication Date: 2025-04-22ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211669839.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-25
Publication Date
2025-04-22
Estimated Expiration
2042-12-25

AI Technical Summary

Technical Problem

The existing photocatalytic materials have problems such as insufficient catalytic sites and limited charge separation capabilities during CO2 reduction, which limits their further practical application in the field of photocatalytics.

Method used

The photocatalytic performance of the material is optimized by dispersing single atoms Mn in the covalent carbon-nitrogen skeleton in a limited domain and constructing an oxidation reaction center through P doping. The method includes self-assembly using organic monomers with aldehyde and amino groups to form a three-dimensional covalent carbon-nitrogen framework, subsequently introducing the P element through hydrothermal reaction, and dispersing the Mn element in the material by ball milling method, and finally improving the coordination stability of the material through high temperature calcination.

Benefits of technology

The high-efficiency photocatalytic CO2 reduction performance of the material is achieved, with rich active sites and separate redox centers, and the selectivity and efficiency of the photocatalyst are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116196979B_ABST
    Figure CN116196979B_ABST
Patent Text Reader

Abstract

The present invention discloses a P-doped covalent carbon-nitrogen skeleton dispersed by a confined single-atom Mn, and a preparation method and application thereof. The covalent carbon-nitrogen skeleton is prepared by dispersing triformylbenzene and ethylenediamine in an organic solvent, transferring to a Pyrex glass tube after degassing by a freeze-pump-thaw cycle, heating to generate a precursor product, and adding the precursor to a mixed solution of phosphoric acid and acetic acid for hydrothermal reaction to form a P-doped covalent carbon-nitrogen skeleton. Finally, the Mn single atom is dispersed in a porous skeleton in the P-doped covalent carbon-nitrogen skeleton by ball milling to form a photocatalyst dispersed by a confined single atom. In the covalent carbon-nitrogen skeleton of the present invention, the P-doped covalent carbon-nitrogen skeleton not only acts as a carrier, but also has excellent light absorption itself. In addition, the highly dispersed single-atom Mn can be used as an active center for CO2 catalytic reduction, and the covalently connected network structure can improve the electron transfer efficiency, has excellent photocatalytic CO2 reduction performance, and can be used in the fields of heterogeneous catalysis, energy environment, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of material preparation and energy chemical industry, and in particular relates to a P-doped covalent carbon-nitrogen skeleton dispersed with confined single-atom Mn, and a preparation method and application thereof. Background Art

[0002] Converting CO2 into fuel using sunlight is a potential solution to global warming and energy supply problems, and is in line with the global green and low-carbon development strategy. However, since the rapid recombination of photogenerated electron-hole pairs cannot simultaneously overcome the high chemical inertness of CO2 molecules and the slow oxidation kinetics of water, there are still great challenges in achieving overall photocatalytic oxidation and reduction reactions. Studies have found that combining the spatial separation of oxidation and reduction centers, rapid electron transfer, and functional interactions achieved through non-metallic doping with metal single atom loading may be a promising strategy to achieve overall photoreactions. However, these strategies have problems such as complex synthesis steps and lack of atomic-scale control, which hinder the industrial application of efficient CO2 reduction photocatalysis.

[0003] Covalent carbon-nitrogen frameworks are considered to be one of the most promising photocatalysts for industrial use due to their excellent chemical stability and low cost, but their weak visible light response affects their efficiency in the photocatalytic process. In recent years, single-atom catalysts have become a research hotspot in the field of materials due to their abundant and well-defined atomic sites, which can be used to regulate the electronic structure of catalysts. The combination of single atoms with covalent carbon-nitrogen frameworks provides new opportunities to solve long-standing problems in the field of photocatalysis. However, the reported single-atom carbon-nitrogen-based photocatalytic materials still have the problems of insufficient catalytic sites and limited charge separation ability, which limits their further practical application in the field of photocatalysis.

[0004] Non-metallic doping can introduce oxidation sites on carbon and nitrogen, which can effectively separate photogenerated holes and charges during CO2 reduction. The selectivity of photocatalytic CO2 reduction can be further improved by finely designing the surface structure of covalent carbon and nitrogen materials. Therefore, it is of great significance to explore new methods to improve non-metallic doping and metal single atom loading on covalent carbon and nitrogen framework materials. Summary of the invention

[0005] In view of the above problems existing in the prior art, the purpose of the present invention is to provide a method for preparing and applying a P-doped covalent carbon-nitrogen skeleton dispersed by a confined single-atom Mn. Compared with other methods, the P-doped covalent carbon-nitrogen skeleton dispersed by a confined single-atom Mn of the present invention has low energy consumption and low pollution during the preparation process, and can be doped with P elements without destroying the skeleton substrate. The Mn element is uniformly confined in the porous structure of the skeleton, and the prepared material is stable and has a large specific surface area, rich active sites and separated redox centers. The P-doped covalent carbon-nitrogen skeleton dispersed by a confined single-atom Mn of the present invention is optimized to have efficient photocatalytic CO2 reduction performance, and has a wide range of applications in energy chemical industry, heterogeneous catalysis and other fields.

[0006] In order to optimize the photocatalytic performance of the covalent carbon-nitrogen skeleton, the present invention adopts a brand-new method to construct a P-doped covalent carbon-nitrogen skeleton dispersed with a confined single-atom Mn: utilizing the difference in chain length of organic monomers having aldehyde groups and amino groups, respectively, polycondensing in an organic solvent to form a three-dimensional covalent carbon-nitrogen skeleton with a porous nanostructure. At the same time, utilizing the difference in electronegativity, the N element in the covalent carbon-nitrogen skeleton is successfully replaced with the phosphorus element to construct an oxidation reaction center. Finally, the Mn element is dispersed in the porous structure of the covalent carbon-nitrogen skeleton in the form of a single atom by a ball milling method, and the coordination stability of Mn with P atoms and C atoms is improved by high-temperature calcination to obtain a P-doped covalent carbon-nitrogen skeleton dispersed with a confined single-atom Mn.

[0007] In terms of the selection of organic monomers, triformylbenzene and ethylenediamine are used as structural building units to ensure photocatalytic performance and realize the transformation from a two-dimensional planar skeleton to a three-dimensional skeleton. The three-dimensional covalent carbon-nitrogen skeleton can not only well encapsulate the monodispersed Mn atoms, but also increase the specific surface area and light absorption efficiency of the material.

[0008] The technical solution adopted by the present invention is as follows:

[0009] The P-doped covalent carbon-nitrogen skeleton with confined single-atom Mn dispersion is self-assembled into a polymer three-dimensional cage structure by organic monomers having aldehyde groups and amino groups respectively, the P element is doped into the material by replacing the N element in the covalent carbon-nitrogen skeleton through a hydrothermal reaction, the Mn element is coordinated with the P and C atoms in the carbon-nitrogen skeleton through ball milling, and is dispersed in the P-doped covalent carbon-nitrogen skeleton in the form of a single atom.

[0010] Furthermore, the self-assembly is carried out by periodic condensation of amino and aldehyde functional groups in an organic solvent to form a regular three-dimensional cage structure; the source of the P element is phosphoric acid, and the hydrothermal reaction is carried out under the protection of acetic acid; the source of the Mn element is potassium permanganate.

[0011] The method for preparing the P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn comprises the following steps:

[0012] S1: Mixing an organic monomer 1 having an aldehyde group and an organic monomer 2 having an amino group in a mixed organic solvent, rapidly freezing the mixture in a liquid nitrogen bath, degassing the mixture through a freeze pump thawing cycle, and then transferring the mixture to a Pyrex glass tube for sealing;

[0013] S2: The Pyrex glass tube is then transferred to an oven and heated to react and generate a precursor product;

[0014] S3: adding the precursor product to a mixed aqueous solution of phosphoric acid and acetic acid for hydrothermal reaction, cooling to room temperature after the reaction is completed, centrifugation, washing, and drying to form a P-doped covalent carbon-nitrogen skeleton material;

[0015] S4: After mixing the P-doped covalent carbon-nitrogen framework material obtained in step S3 with a Mn source and ball-milling the mixture, the mixture is transferred to a tubular furnace and calcined under an inert atmosphere to obtain a P-doped covalent carbon-nitrogen framework with confined single-atom Mn dispersed therein.

[0016] Furthermore, in step S1, the organic monomer 1 having an aldehyde group is triformylbenzene, the organic monomer 2 having an amino group is ethylenediamine, and the molar ratio of the organic monomer 1 to the organic monomer 2 is 1:0.5-2, preferably 1:1.

[0017] Furthermore, in step S1, the mixed organic solvent is a mixture of dioxane, tetrahydrofuran and methanol, and the volume ratio of the three is 1-4: 0.5-2: 6, preferably 2: 1: 6.

[0018] Furthermore, in step S1, the concentration of the organic monomer 1 having an aldehyde group and the organic monomer 2 having an amino group in the mixed organic solvent is 0.3-1.0 mol / L, preferably 0.6-0.7 mol / L.

[0019] Furthermore, in step S2, the precursor product is heated in an oven, and the temperature of the oven is set to 80-120° C., preferably 100° C.; the heating time is controlled to 1.5-2.5 h, preferably 2.0 h.

[0020] Furthermore, in the mixed aqueous solution of phosphoric acid and acetic acid in step S3, the concentration of phosphoric acid is controlled at 2.0~3.0 mol / L, preferably 2.5 mol / L; the concentration of acetic acid is 0.2~0.8 mol / L, preferably 0.5 mol / L; the ratio of the mass of the precursor product in step S3 to the amount of phosphoric acid is 1:2~3, preferably 1:2.5, the unit of mass is mg, and the unit of amount of substance is mmol.

[0021] Furthermore, in step S4, the Mn source is potassium permanganate, and the mass ratio of the P-doped covalent carbon-nitrogen skeleton to the Mn source is 1:10-30, preferably 1:20; and the ball milling time is controlled at 3.0-5.0 h, preferably 4.0 h.

[0022] Furthermore, in the tubular furnace calcination in step S4, the tubular furnace needs to be pre-vacuumed; the calcination atmosphere is argon; the calcination temperature is controlled at 180-220°C, preferably 200°C; and the calcination time is controlled at 1.5-2.5 h, preferably 2.0 h.

[0023] The application of the confined single-atom Mn-dispersed P-doped covalent carbon-nitrogen framework in photocatalytic CO2 reduction.

[0024] The present invention provides a green synthesis method of a P-doped covalent carbon-nitrogen framework dispersed with a confined single-atom Mn atom. As an optimized P-doped covalent carbon-nitrogen framework dispersed with a confined single-atom Mn atom, the material can realize efficient photocatalytic reduction of CO2.

[0025] The P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn of the present invention has the following advantages in implementation:

[0026] 1) Compared with traditional covalent carbon-nitrogen skeleton-based materials, the doping of P element broadens its light absorption capacity under visible light. It can be used as an oxidation site to capture photogenerated holes and become an oxidation site for the reaction. In the P-doped covalent carbon-nitrogen skeleton dispersed with confined single-atom Mn prepared by the present invention, the P-doped covalent carbon-nitrogen skeleton not only acts as a carrier, but also has excellent light absorption itself. In addition, the highly dispersed single-atom Mn can be used as the active center for CO2 catalytic reduction, and the covalently connected network structure can improve the electron transfer efficiency, has excellent photocatalytic CO2 reduction performance, and can be used in heterogeneous catalysis, energy environment and other fields.

[0027] 2) The dispersion of single-atom Mn improves the ability to transfer photogenerated electrons from the carbon-nitrogen skeleton to metal sites, which can serve as a reduction site to capture photogenerated holes and promote the photocatalytic CO2 reduction.

[0028] 3) Since the P-doped covalent carbon-nitrogen framework with confined single-atom Mn dispersion in the present invention is easy to prepare and has high efficiency and selectivity in photocatalytic CO2 reduction, it has great application potential in fields such as energy development. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a high-resolution transmission electron microscopy image of the P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn prepared in Example 1;

[0030] Figure 2This is a high-resolution transmission electron microscopy image of the P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn prepared in Example 3;

[0031] Figure 3 This is a high-resolution transmission electron microscopy image of the P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn prepared in Example 6. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0033] In the following examples, triformylbenzene, ethylenediamine, dioxane and potassium permanganate were purchased from Beijing Bailingwei Technology Co., Ltd. without further purification; tetrahydrofuran, methanol, phosphoric acid and acetic acid were purchased from Shanghai MacLean Biochemical Technology Co., Ltd. without further purification.

[0034] Of course, those skilled in the art will appreciate that the selection of this raw material is only a preferred embodiment of the present invention, and each parameter can be adjusted according to actual needs. Triformylbenzene and ethylenediamine can be substituted with other organic monomers having an aldehyde group and an amino group. Therefore, the replacement of the raw material can also achieve the effect of the present invention to a certain extent, and should also fall within the protection scope of the present invention. Specific embodiments are as follows:

[0035] Example 1

[0036] In this embodiment, the specific steps of preparing a P-doped covalent carbon-nitrogen framework with confined single-atom Mn dispersion are as follows:

[0037] (1) Add triformylbenzene (5.0 mmol) and ethylenediamine (5.0 mmol) to a mixture of dioxane (2.0 mL), tetrahydrofuran (1.0 mL) and methanol (6 mL) at room temperature and stir for 30 min to mix thoroughly.

[0038] (2) The solution obtained in step (1) was rapidly frozen in a liquid nitrogen bath (77 K), degassed by three freeze-pump-thaw cycles, and then transferred to a Pyrex glass tube and sealed.

[0039] (3) Transfer the Pyrex glass tube to a forced air drying oven at 100 °C for 2.0 h.

[0040] (4) The product was cooled to room temperature by centrifugation, washed with methanol and water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0041] (5) The dried material (50 mg) from step (4) was added to a mixed aqueous solution (50 mL) of phosphoric acid (2.5 mol / L) and acetic acid (0.5 mol / L) and ultrasonically dispersed for 30 min. The mixture was then transferred to a 100 mL reactor and placed in an oven at 150 °C for 2.0 h.

[0042] (6) The reactants were cooled to room temperature and centrifuged, washed with water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0043] (7) Potassium permanganate (2.0 mg) and the dried material (40.0 mg) from step (6) were ball milled for 4.0 h and then transferred to a pre-evacuated tube furnace and kept at 200 °C under argon atmosphere for 2.0 h.

[0044] (8) Finally, the obtained material was washed three times in methanol and water and then transferred to a 60°C vacuum drying oven for drying overnight. The high-resolution transmission electron microscopy image of the P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn prepared in Example 1 is shown in FIG. Figure 1 .

[0045] Example 2

[0046] In this embodiment, the specific steps of preparing a P-doped covalent carbon-nitrogen framework with confined single-atom Mn dispersion are as follows:

[0047] (1) Add triformylbenzene (5.0 mmol) and ethylenediamine (5.0 mmol) to a mixture of dioxane (2.0 mL), tetrahydrofuran (1.0 mL) and methanol (6 mL) at room temperature and stir for 30 min to mix thoroughly.

[0048] (2) The solution obtained in step (1) was rapidly frozen in a liquid nitrogen bath (77 K), degassed by three freeze-pump-thaw cycles, and then transferred to a Pyrex glass tube and sealed.

[0049] (3) Transfer the Pyrex glass tube to a forced air drying oven at 100 °C for 2.0 h.

[0050] (4) The product was cooled to room temperature by centrifugation, washed with methanol and water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0051] (5) The dried material (50 mg) from step (4) was added to a mixed aqueous solution (50 mL) of phosphoric acid (2.0 mol / L) and acetic acid (0.5 mol / L) and ultrasonically dispersed for 30 min. The mixture was then transferred to a 100 mL reactor and placed in an oven at 150 °C for 2.0 h.

[0052] (6) The reactants were cooled to room temperature and centrifuged, washed with water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0053] (7) Potassium permanganate (2.0 mg) and the dried material (40.0 mg) from step (6) were ball milled for 4.0 h and then transferred to a pre-evacuated tube furnace and kept at 200 °C under argon atmosphere for 2.0 h.

[0054] (8) Finally, the obtained material was washed three times in methanol and water and then transferred to a vacuum drying oven at 60 °C and dried overnight.

[0055] Example 3

[0056] In this embodiment, the specific steps of preparing a P-doped covalent carbon-nitrogen framework with confined single-atom Mn dispersion are as follows:

[0057] (1) Add triformylbenzene (5.0 mmol) and ethylenediamine (5.0 mmol) to a mixture of dioxane (2.0 mL), tetrahydrofuran (1.0 mL) and methanol (6 mL) at room temperature and stir for 30 min to mix thoroughly.

[0058] (2) The solution obtained in step (1) was rapidly frozen in a liquid nitrogen bath (77 K), degassed by three freeze-pump-thaw cycles, and then transferred to a Pyrex glass tube and sealed.

[0059] (3) Transfer the Pyrex glass tube to a forced air drying oven at 100 °C for 2.0 h.

[0060] (4) The product was cooled to room temperature by centrifugation, washed with methanol and water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0061] (5) The dried material (50 mg) obtained in step (4) was added to a mixed aqueous solution (50 mL) of phosphoric acid (3.0 mol / L) and acetic acid (0.5 mol / L) and ultrasonically dispersed for 30 min. The mixture was then transferred to a 100 mL reactor and placed in an oven at 150 °C for 2.0 h.

[0062] (6) The reactants were cooled to room temperature and centrifuged, washed with water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0063] (7) Potassium permanganate (2.0 mg) and the dried material (40.0 mg) from step (6) were ball milled for 4.0 h and then transferred to a pre-evacuated tube furnace and kept at 200 °C under argon atmosphere for 2.0 h.

[0064] (8) Finally, the obtained material was washed three times in methanol and water and then transferred to a 60°C vacuum drying oven for drying overnight. The high-resolution transmission electron microscopy image of the P-doped covalent carbon-nitrogen framework with confined single-atom Mn dispersion prepared in Example 3 is shown in FIG. Figure 2 .

[0065] Example 4

[0066] In this embodiment, the specific steps of preparing a P-doped covalent carbon-nitrogen framework with confined single-atom Mn dispersion are as follows:

[0067] (1) Add triformylbenzene (5.0 mmol) and ethylenediamine (5.0 mmol) to a mixture of dioxane (2.0 mL), tetrahydrofuran (1.0 mL) and methanol (6 mL) at room temperature and stir for 30 min to mix thoroughly.

[0068] (2) The solution obtained in step (1) was rapidly frozen in a liquid nitrogen bath (77 K), degassed by three freeze-pump-thaw cycles, and then transferred to a Pyrex glass tube and sealed.

[0069] (3) Transfer the Pyrex glass tube to a forced air drying oven at 80 °C for 2.0 h.

[0070] (4) The product was cooled to room temperature by centrifugation, washed with methanol and water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0071] (5) The dried material (50 mg) from step (4) was added to a mixed aqueous solution (50 mL) of phosphoric acid (2.5 mol / L) and acetic acid (0.5 mol / L) and ultrasonically dispersed for 30 min. The mixture was then transferred to a 100 mL reactor and placed in an oven at 150 °C for 2.0 h.

[0072] (6) The reactants were cooled to room temperature and centrifuged, washed with water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0073] (7) Potassium permanganate (2.0 mg) and the dried material (40.0 mg) from step (6) were ball milled for 4.0 h and then transferred to a pre-evacuated tube furnace and kept at 200 °C under argon atmosphere for 2.0 h.

[0074] (8) Finally, the obtained material was washed three times in methanol and water and then transferred to a vacuum drying oven at 60 °C and dried overnight.

[0075] Example 5

[0076] In this embodiment, the specific steps of preparing a P-doped covalent carbon-nitrogen framework with confined single-atom Mn dispersion are as follows:

[0077] (1) Add triformylbenzene (5.0 mmol) and ethylenediamine (5.0 mmol) to a mixture of dioxane (2.0 mL), tetrahydrofuran (1.0 mL) and methanol (6 mL) at room temperature and stir for 30 min to mix thoroughly.

[0078] (2) The solution obtained in step (1) was rapidly frozen in a liquid nitrogen bath (77 K), degassed by three freeze-pump-thaw cycles, and then transferred to a Pyrex glass tube and sealed.

[0079] (3) Transfer the Pyrex glass tube to a forced air drying oven at 120 °C for 2.0 h.

[0080] (4) The product was cooled to room temperature by centrifugation, washed with methanol and water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0081] (5) The dried material (50 mg) from step (4) was added to a mixed aqueous solution (50 mL) of phosphoric acid (2.5 mol / L) and acetic acid (0.5 mol / L) and ultrasonically dispersed for 30 min. The mixture was then transferred to a 100 mL reactor and placed in an oven at 150 °C for 2.0 h.

[0082] (6) The reactants were cooled to room temperature and centrifuged, washed with water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0083] (7) Potassium permanganate (2.0 mg) and the dried material (40.0 mg) from step (6) were ball milled for 4.0 h and then transferred to a pre-evacuated tube furnace and kept at 200 °C under argon atmosphere for 2.0 h.

[0084] (8) Finally, the obtained material was washed three times in methanol and water and then transferred to a vacuum drying oven at 60 °C and dried overnight.

[0085] Example 6

[0086] In this embodiment, the specific steps of preparing a P-doped covalent carbon-nitrogen framework with confined single-atom Mn dispersion are as follows:

[0087] (1) Add triformylbenzene (5.0 mmol) and ethylenediamine (5.0 mmol) to a mixture of dioxane (2.0 mL), tetrahydrofuran (1.0 mL) and methanol (6 mL) at room temperature and stir for 30 min to mix thoroughly.

[0088] (2) The solution obtained in step (1) was rapidly frozen in a liquid nitrogen bath (77 K), degassed by three freeze-pump-thaw cycles, and then transferred to a Pyrex glass tube and sealed.

[0089] (3) Transfer the Pyrex glass tube to a forced air drying oven at 100 °C for 2.0 h.

[0090] (4) The product was cooled to room temperature by centrifugation, washed with methanol and water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0091] (5) The dried material (50 mg) from step (4) was added to a mixed aqueous solution (50 mL) of phosphoric acid (2.5 mol / L) and acetic acid (0.5 mol / L) and ultrasonically dispersed for 30 min. The mixture was then transferred to a 100 mL reactor and placed in an oven at 150 °C for 2.0 h.

[0092] (6) The reactants were cooled to room temperature and centrifuged, washed with water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0093] (7) Potassium permanganate (2.0 mg) and the dried material (40.0 mg) from step (6) were ball milled for 4.0 h and then transferred to a pre-evacuated tube furnace and kept at 220 °C under argon atmosphere for 2.0 h.

[0094] (8) Finally, the obtained material was washed three times in methanol and water and then transferred to a 60°C vacuum drying oven for drying overnight. The high-resolution transmission electron microscopy image of the P-doped covalent carbon-nitrogen framework with confined single-atom Mn dispersion prepared in Example 6 is shown in FIG. Figure 3 .

[0095] Figure 1 It can be seen that the synthesized confined single-atom Mn-dispersed P-doped covalent carbon-nitrogen framework has an obvious spherical porous structure, good stratification, perfect porous structure and high transmittance.

[0096] Figure 2 The synthesized confined single-atom Mn-dispersed P-doped covalent carbon-nitrogen framework also has an obvious spherical porous structure, a thick layered structure, a perfect porous structure, and a slightly reduced transmittance.

[0097] Figure 3The synthesized confined single-atom Mn-dispersed P-doped covalent carbon-nitrogen skeleton has an unclear spherical porous structure, a slightly collapsed layered structure, a destroyed porous structure, and an acceptable light transmittance.

[0098] Example 7

[0099] In this embodiment, the specific steps of preparing a P-doped covalent carbon-nitrogen framework are as follows:

[0100] (1) Add triformylbenzene (5.0 mmol) and ethylenediamine (5.0 mmol) to a mixture of dioxane (2.0 mL), tetrahydrofuran (1.0 mL) and methanol (6 mL) at room temperature and stir for 30 min to mix thoroughly.

[0101] (2) The solution obtained in step (1) was rapidly frozen in a liquid nitrogen bath (77 K), degassed by three freeze-pump-thaw cycles, and then transferred to a Pyrex glass tube and sealed.

[0102] (3) Transfer the Pyrex glass tube to a forced air drying oven at 100 °C for 2.0 h.

[0103] (4) The product was cooled to room temperature by centrifugation, washed with methanol and water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0104] (5) The dried material (50 mg) from step (4) was added to a mixed aqueous solution (50 mL) of phosphoric acid (2.5 mol / L) and acetic acid (0.5 mol / L) and ultrasonically dispersed for 30 min. The mixture was then transferred to a 100 mL reactor and placed in an oven at 150 °C for 2.0 h.

[0105] (6) The reactants were cooled to room temperature and centrifuged, washed with water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0106] Example 8

[0107] In this embodiment, the specific steps of preparing a P-doped covalent carbon-nitrogen framework with confined single-atom Mn dispersion are as follows:

[0108] (1) Add triformylbenzene (5.0 mmol) and ethylenediamine (5.0 mmol) to a mixture of dioxane (2.0 mL), tetrahydrofuran (1.0 mL) and methanol (6 mL) at room temperature and stir for 30 min to mix thoroughly.

[0109] (2) The solution obtained in step (1) was rapidly frozen in a liquid nitrogen bath (77 K), degassed by three freeze-pump-thaw cycles, and then transferred to a Pyrex glass tube and sealed.

[0110] (3) Transfer the Pyrex glass tube to a forced air drying oven at 100 °C for 2.0 h.

[0111] (4) The product was cooled to room temperature by centrifugation, washed with methanol and water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0112] (5) The dried material (50 mg) from step (4) was added to a mixed aqueous solution (50 mL) of phosphoric acid (2.5 mol / L) and acetic acid (0.5 mol / L) and ultrasonically dispersed for 30 min. The mixture was then transferred to a 100 mL reactor and placed in an oven at 150 °C for 2.0 h.

[0113] (6) The reactants were cooled to room temperature and centrifuged, washed with water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0114] (7) Potassium permanganate (1.0 mg) and the dried material (40.0 mg) from step (6) were ball milled for 4.0 h and then transferred to a pre-evacuated tube furnace and kept at 200 °C under argon atmosphere for 2.0 h.

[0115] (8) Finally, the obtained material was washed three times in methanol and water and then transferred to a vacuum drying oven at 60 °C and dried overnight.

[0116] Example 9

[0117] In this embodiment, the specific steps of preparing a P-doped covalent carbon-nitrogen framework with confined single-atom Mn dispersion are as follows:

[0118] (1) Add triformylbenzene (5.0 mmol) and ethylenediamine (5.0 mmol) to a mixture of dioxane (2.0 mL), tetrahydrofuran (1.0 mL) and methanol (6 mL) at room temperature and stir for 30 min to mix thoroughly.

[0119] (2) The solution obtained in step (1) was rapidly frozen in a liquid nitrogen bath (77 K), degassed by three freeze-pump-thaw cycles, and then transferred to a Pyrex glass tube and sealed.

[0120] (3) Transfer the Pyrex glass tube to a forced air drying oven at 100 °C for 2.0 h.

[0121] (4) The product was cooled to room temperature by centrifugation, washed with methanol and water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0122] (5) The dried material (50 mg) from step (4) was added to a mixed aqueous solution (50 mL) of phosphoric acid (2.5 mol / L) and acetic acid (0.5 mol / L) and ultrasonically dispersed for 30 min. The mixture was then transferred to a 100 mL reactor and placed in an oven at 150 °C for 2.0 h.

[0123] (6) The reactants were cooled to room temperature and centrifuged, washed with water three times, and then transferred to a 60 °C vacuum drying oven and dried overnight.

[0124] (7) Potassium permanganate (3.0 mg) and the dried material (40.0 mg) from step (6) were ball milled for 4.0 h and then transferred to a pre-evacuated tube furnace and kept at 200 °C under argon atmosphere for 2.0 h.

[0125] (8) Finally, the obtained material was washed three times in methanol and water and then transferred to a vacuum drying oven at 60 °C and dried overnight.

[0126] Application Examples

[0127] The P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn obtained in Examples 1 to 9 was used to carry out a photocatalytic CO2 reduction experiment under simulated sunlight.

[0128] The experimental conditions are as follows: 20 mg of photocatalyst was added to 100 mL of a mixed solution of acetonitrile, TEOA and water for ultrasonic dispersion; pure CO2 was bubbled into the solution for 20 min to saturate the solution with CO2. The solution was then placed in a homemade photoreactor and irradiated under a 300 W xenon lamp with an ultraviolet filter (λ≥420 nm). After 1 h of illumination, the gas was monitored and analyzed online by a gas chromatograph (GC9790II).

[0129] The performance of the confined single-atom Mn-dispersed P-doped covalent carbon-nitrogen skeleton photocatalytic CO2 reduction prepared in different embodiments is shown in Table 1.

[0130] By comparing Example 1, Example 2 and Example 3, it can be found that increasing and decreasing the concentration of phosphoric acid will cause a slight decrease in the performance of the photocatalytic CO2 reduction of the material, which may be due to the lack of active sites or the decrease in material stability. By comparing Example 1, Example 4 and Example 5, it can be found that increasing the temperature of the condensation of the raw materials in the Pyrex glass tube also causes a decrease in the performance of the photocatalytic CO2 reduction, which may be due to the incomplete condensation of the organic monomers caused by low or high temperatures. By comparing Example 1 and Example 6, it can be found that increasing the temperature of calcination in a tubular furnace has a significant effect on the performance of the photocatalyst CO2 reduction, which may be due to the carbonization of the material surface or the collapse of the three-dimensional covalent carbon-nitrogen skeleton caused by the temperature. By comparing Examples 1 and 7, it can be found that without the addition of Mn metal by ball milling, the rate of photocatalytic CO2 of the P-doped covalent carbon-nitrogen skeleton drops sharply, and the rate of generating CO is only 12.2 μmol / g / h, which indicates that Mn doping is the main active site for photocatalytic CO2 reduction. By comparing Example 1, Example 8 and Example 9, it can be found that increasing or decreasing the Mn doping content reduces the photocatalytic performance of the Mn-dispersed P-doped covalent carbon-nitrogen skeleton, which proves that the appropriate Mn doping amount is also the reason for ensuring its efficient catalytic performance.

[0131]

[0132] The above-described embodiment is only a preferred scheme of the present invention, but it is not intended to limit the present invention. For example, although in the above-described embodiment, the raw material in the preparation process is triformylbenzene and ethylenediamine, it does not mean that it must adopt these two organic ligands, as long as the organic ligand with aldehyde group and amino group can be selected, in theory, polyreaction can be carried out in an organic solvent according to the above method to generate a carbon-nitrogen copolymer. Also for example, although the protective gas tested in the above-described embodiment when high-temperature calcining is argon, it does not mean that argon can only be used to achieve effect of the present invention, adopting an inert gas, such as nitrogen, in the high-temperature calcining process, the protective material is not destroyed, and effect of the present invention can be achieved.

[0133] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.

Claims

1. A P-doped covalent carbon-nitrogen framework with confined single-atom Mn dispersion, characterized in that: The covalent carbon-nitrogen skeleton is a three-dimensional polymer cage structure self-assembled by organic monomers with aldehyde groups and amino groups. The P element is doped into the material by replacing the N element in the covalent carbon-nitrogen skeleton through a hydrothermal reaction. The Mn element is coordinated with the P and C atoms in the carbon-nitrogen skeleton by ball milling and dispersed in the P-doped covalent carbon-nitrogen skeleton in the form of single atoms. The self-assembly is carried out by condensing the periodic amino and aldehyde functional groups into a regular three-dimensional cage structure in an organic solvent; the source of the P element is phosphoric acid, and the hydrothermal reaction is carried out under the protection of acetic acid; the source of the Mn element is potassium permanganate; The confined single-atom Mn-dispersed P-doped covalent carbon-nitrogen framework is prepared by the following steps: S1: Mixing an organic monomer having an aldehyde group and an organic monomer having an amino group in a mixed organic solvent, rapidly freezing the mixed solution in a liquid nitrogen bath environment, and transferring the mixture to a Pyrex glass tube for sealing after degassing through a freezing pump thawing cycle; the organic monomer having an aldehyde group is triformylbenzene, and the organic monomer having an amino group is ethylenediamine; S2: The Pyrex glass tube is then transferred to an oven and heated to react and generate a precursor product; S3: adding the precursor product to a mixed aqueous solution of phosphoric acid and acetic acid for hydrothermal reaction, cooling to room temperature after the reaction is completed, centrifugation, washing, and drying to form a P-doped covalent carbon-nitrogen skeleton material; S4: After mixing the P-doped covalent carbon-nitrogen framework material obtained in step S3 with a Mn source and ball-milling the mixture, the mixture is transferred to a tubular furnace and calcined under an inert atmosphere to obtain a P-doped covalent carbon-nitrogen framework with confined single-atom Mn dispersion; the tubular furnace is calcined and the tubular furnace needs to be pre-vacuumed; the calcination atmosphere is argon; the calcination temperature is controlled at 180-220°C, and the calcination time is controlled at 1.5-2.5 h.

2. The P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn as claimed in claim 1, characterized in that: In step S1, the molar ratio of the organic monomer 1 to the organic monomer 2 is 1:0.5-2.

3. The P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn as claimed in claim 2, characterized in that: In step S1, the molar ratio of the organic monomer 1 to the organic monomer 2 is 1:

1.

4. The P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn as claimed in claim 1, characterized in that: In step S1, the mixed organic solvent is a mixture of dioxane, tetrahydrofuran and methanol, the volume ratio of the three is 1-4:0.5-2:6, and the concentrations of the organic monomer 1 having an aldehyde group and the organic monomer 2 having an amino group in the mixed organic solvent are both 0.3-1.0 mol / L.

5. The P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn as claimed in claim 4, characterized in that: In step S1, dioxane, tetrahydrofuran and methanol are mixed in an organic solvent in a volume ratio of 2:1:6; the concentrations of the first organic monomer having an aldehyde group and the second organic monomer having an amino group in the mixed organic solvent are both 0.6-0.7 mol / L.

6. The P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn as claimed in claim 1, characterized in that: In step S2, the precursor product is heated in an oven, the temperature of the oven is set to 80-120° C., and the heating time is controlled to be 1.5-2.5 h.

7. The P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn as claimed in claim 6, characterized in that: In step S2, the temperature of the oven is set to 100°C; the heating time is controlled at 2.0 h.

8. The P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn as claimed in claim 1, characterized in that: In the mixed aqueous solution of phosphoric acid and acetic acid in step S3, the concentration of phosphoric acid is controlled to be 2.0-3.0 mol / L, and the concentration of acetic acid is 0.2-0.8 mol / L.

9. The P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn as claimed in claim 8, characterized in that: In the mixed aqueous solution of phosphoric acid and acetic acid in step S3, the concentration of phosphoric acid is controlled at 2.5 mol / L; the concentration of acetic acid is 0.5 mol / L.

10. The P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn as claimed in claim 1, characterized in that: In step S3, the ratio of the mass of the precursor product to the amount of phosphoric acid is 1:2-3, the unit of mass is mg, and the unit of amount of phosphoric acid is mmol.

11. The P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn as claimed in claim 10, characterized in that: The ratio of the mass of the precursor product to the amount of phosphoric acid in step S3 is 1:2.5, the unit of mass is mg, and the unit of amount of phosphoric acid is mmol.

12. The P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn as claimed in claim 1, characterized in that: In step S4, the Mn source is potassium permanganate, the mass ratio of the P-doped covalent carbon-nitrogen skeleton to the Mn source is 1:10-30, and the ball milling time is controlled at 3.0-5.0 h.

13. The P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn as claimed in claim 12, characterized in that: In step S4, the mass ratio of the P-doped covalent carbon-nitrogen framework to the Mn source is 1:20; and the ball milling time is controlled at 4.0 h.

14. The P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn as claimed in claim 1, characterized in that: In step S4, the calcination temperature is controlled at 200°C; and the calcination time is controlled at 2.0 h.

15. Use of the P-doped covalent carbon-nitrogen framework dispersed with confined single-atom Mn as claimed in claim 1 in photocatalytic CO2 reduction.

Citation Information

Patent Citations

  • Monatomic catalyst prepared based on surface immobilizing method

    CN111013576A

  • Preparation method and application of transition metal single atom and nitrogen and phosphorus doped carbon spheres

    CN113410479A